Título Padrão: THE CASE OF A BRAZILIAN CURRICULUM - Alves Araujo, Gilberto; da Silva Freitas, Gizélia Maria (Revista de Letras, 2024)
This paper intends to explore discursive representations by a Curricular Proposal for English teaching from Northern Brazil. It considers not just the authors of the curriculum and representations of English teaching in high school but also the discursive roles played by teachers in that text. It also resorts to French Discourse Analysis and its concepts of forgetting subjection and ideological and discursive formation. The methodology is based on procedures by Orlandi. Preliminary results indicate that the state’s curriculum represents English teaching through a vast horizon of expectations regarding its relevance, validity, and everyday impact. The document tends to overvalue scientific-literary discourse while silencing teachers’ voices in/and their day-to-day praxis. The curriculum also tries to find in a capitalist economic system the reasons that might justify English teaching within a deeply rural and socioeconomically fragile region. The identities of the writers of the document seem to reveal themselves through several contradictions between entireness and dispersion.